2016
DOI: 10.15376/biores.11.2.3614-3625
|View full text |Cite
|
Sign up to set email alerts
|

The Furfurylation of Wood: A Nanomechanical Study of Modified Wood Cells

Abstract: Furfurylation of wood is of interest worldwide as an environmentally friendly modification process. It is widely assumed that low-molecular weight furfuryl alcohol (FA) can penetrate into wood cells and polymerize in-situ during the process, resulting in substantial improvement in the physical-mechanical properties and durability of wood. In this study, confocal laser scanning microscopy (CLSM) was used to visualize the microscopic distribution of polymerized FA resin in the Masson pine wood cavities, and a Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Even today, the question of whether furfurylation is a distinct chemical modification process remains unanswered. Some scientists believe that it comprises a chemical modification process, since the furfuryl alcohol polymer reacts with itself and possibly reacts with the lignin in the cell walls , Nordstierna et al 2008, Gérardin 2016, Li et al 2016. Thus, the furfuryl alcohol complexes are predominantly deposited in the wood cavities and cell walls (Fig.…”
Section: Furfurylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even today, the question of whether furfurylation is a distinct chemical modification process remains unanswered. Some scientists believe that it comprises a chemical modification process, since the furfuryl alcohol polymer reacts with itself and possibly reacts with the lignin in the cell walls , Nordstierna et al 2008, Gérardin 2016, Li et al 2016. Thus, the furfuryl alcohol complexes are predominantly deposited in the wood cavities and cell walls (Fig.…”
Section: Furfurylationmentioning
confidence: 99%
“…Polymerisation takes place in microscopic cell cavities and is easily detected using optical microscopy. Recent nanoindentation studies have indicated that improvements in indentation modulus and hardness of furfurylated wood cells demonstrate indirectly, but strongly, that furfuryl alcohol penetrates wood cells during the modification process (Li et al 2016). Another perception is that furfurylation leads to a permanent "bulking" of the cell wall, meaning that the cells are swollen in a permanent way.…”
Section: Furfurylationmentioning
confidence: 99%
“…Recent nanoindentation studies demonstrated improvements in indentation modulus and hardness of furfurylated wood cells demonstrated. The work indicated that furfuryl alcohol indeed penetrated wood cells during the modification process (Li et al 2016). Another perception is that furfurylation leads to permanent 'bulking' of cell wall, meaning that the cells are swollen in a permanent way.…”
Section: Furfurylationmentioning
confidence: 97%
“…The question of whether wood furfurylation is a true chemical modification of the cell wall remains unanswered by the scientific community. Some scientists believe that it comprises a chemical modification process, since the furfuryl alcohol polymer reacts with itself and possibly reacts with lignin in the cell walls (Nordstierma et al 2008;Lande et al 2008;Li et al 2016;Gérardin 2016). Hence, the furfuryl alcohol complexes are predominantly deposited in the wood cavities, and also in the cell walls (Fig.…”
Section: Furfurylationmentioning
confidence: 99%
“…Furfurylation is a promising green and sustainable process that is capable of simultaneously improving the physical, mechanical, and durable properties of wood [17,18]. Furfurylation has been proven to have a markedly positive influence on the dimensional stability and biological resistance of wood [19][20][21][22]. In this process, furfuryl alcohol (FA), a strong polar and low molecular weight organic chemical derived from corncobs or sugar cane residues [23], is impregnated into wood cavities [24].…”
Section: Introductionmentioning
confidence: 99%